Hepatocyte-derived exosomal miR-27a activateshepatic stellate cells through the inhibitionof PINK1-mediated mitophagy in MAFLD - Xin Luo (Elsevier, 2021)
The role of exosome-mediated mitophagy in the crosstalk between hepatocytes (HCs) and hepatic stellate cells (HSCs) in metabolic-associated fatty liver disease (MAFLD) remains unknown. Serum exosomal miR-27a levels were markedly increased and positively correlated with liver fibrosis in MAFLD patients and mice. Exosomal miR-27a was released from lipotoxic HCs and specifically transmitted to recipient-activated HSCs. PINK1, the key target of miR-27a, primarily mediates mitophagy. Overexpression of miR-27a or knockdown of PINK1 or lipotoxic HC-exosomal miR-27a impaired mitochondria (inhibiting mitophagy, respiration, membrane potential, and transcription while promoting reactive oxygen species production) in activated HSCs and stimulated HSC-derived fibroblasts (promoting activation and proliferation while inhibiting autophagy). High exosomal miR-27a serum levels and a lack of hepatic PINK1-mediated mitophagy were directly related to liver fibrosis in MAFLD mice. Lipotoxic HC exosome transplantation aggravated the degree of PINK1-mediated mitophagy suppression, steatohepatitis, lipidosis, and fibrosis in the livers of MAFLD mice with cirrhosis. Both in vitro and in vivo, exosomes derived from miR-27a-knockdown HCs could not facilitate the abovementioned deteriorating effects. In conclusion, lipotoxic HC-exosomal miR-27a plays a pivotal role in inhibiting mitophagy and in promoting MAFLD-related liver fibrosis by negatively regulating PINK1 expression.